Comparative review of existing building performance assessment systems: appropriateness for the context of emerging/developing countries - Shari, Zalina; Soebarto, Veronica (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
Emerging/developing countries have begun to realize that the implementation of building performance assessment systems (BPASs) have the potential to contribute towards achieving a sustainable built environment. Consequently, some BPASs from developed countries have been adopted or customized to be implemented in emerging/developing countries, including Malaysia. The objectives of this paper are to: 1) analyse the effectiveness of existing BPASs in assessing building sustainability in emerging/developing countries; and 2) investigate their appropriateness in addressing the Malaysian context. The paper comparatively reviews and critiques nine BPASs in terms of their characteristics and limitations by analysing the content of the systems’ documentation as well as reviewing other documents related to the systems. Overall, the study finds that most existing BPASs are inadequate in addressing the complex concept of sustainability as well as many of the non-environmental priorities of emerging/developing countries, particularly Malaysia. In fact, priority issues of BPASs from emerging/developing nations reviewed in this paper still reflect those of developed countries. This paper concludes by recommending the specific requirements for developing the Malaysian office building sustainability assessment framework. These findings provide an appropriate basis for other emerging/developing countries to establish a country-specific building sustainability assessment framework that takes relevant priorities into account.